Identifikasi Intrusi Air Laut pada Air Tanah Menggunakan Metode Geolistrik Tahanan Jenis Wenner-Schlumberger (2D) di Pulau Balu, Desa Santiri, Kecamatan Tiworo Utara, Kabupaten Muna Barat - Ikhsan Cahyadi; Syamsul Razak Haraty; La Ode Ihksan Juarzan (Jurnal Rekayasa Geofisika Indonesia, 2024)
This research aims to identify sea water intrusion in groundwater using the Wenner-Schlumberger configuration (2D) resistivity geolectric method on Balu Island, Santiri village, Tiworo Utara sub-District, West Muna Regency. This research uses primary data which is resistivty measurement data measured in the field aimed at identifying groundwater aquifers. The interpretation data is then reconstructed into 2D cross-sectional profile using Res2Dinv software. The results obtained in the research area show that sea water intrusion has occurred in groundwater at an average surface depth of up to 39.6 meters with low resistivity values ​​between 0.06 – 807 Ohm-meters